The Plasma Lipidomic Signature of Nonalcoholic Steatohepatitis - Puri, Puneet (Hepatology, 2009)
Specific alterations in hepatic lipid composition characterize the spectrum of nonalcoholic fatty liver disease (NAFLD), which extends from nonalcoholic fatty liver (NAFL) to nonalcoholic steatohepatitis (NASH). However, the plasma lipidome of NAFLD and whether NASH has a distinct plasma lipidomic signature are unknown. A comprehensive analysis of plasma lipids and eicosanoid metabolites quantified by mass spectrometry was performed in NAFL (n = 25) and NASH (n = 50) subjects and compared with lean normal controls (n = 50). The key findings include significantly increased total plasma monounsaturated fatty acids driven by palmitoleic (16:1 n7) and oleic (18:1 n9) acids content (P < 0.01 for both acids in both NAFL and NASH). The levels of palmitoleic acid, oleic acid, and palmitoleic acid to palmitic acid (16:0) ratio were significantly increased in NAFLD across multiple lipid classes. Linoleic acid (8:2n6) was decreased (P < 0.05), with a concomitant increase in γ-linolenic (18:3n6) and dihomo γ-linolenic (20:3n6) acids in both NAFL and NASH (P < 0.001 for most lipid classes). The docosahexanoic acid (22:6 n3) to docosapentenoic acid (22:5n3) ratio was significantly decreased within phosphatidylcholine (PC), and phosphatidylethanolamine (PE) pools, which was most marked in NASH subjects (P < 0.01 for PC and P < 0.001 for PE). The total plasmalogen levels were significantly decreased in NASH compared with controls (P < 0.05). A stepwise increase in lipoxygenase (LOX) metabolites 5(S)-hydroxyeicosatetraenoic acid (5-HETE), 8-HETE, and 15-HETE characterized progression from normal to NAFL to NASH. The level of 11-HETE, a nonenzymatic oxidation product of arachidonic (20:4) acid, was significantly increased in NASH only. Conclusions: Although increased lipogenesis, desaturases, and LOX activities characterize NAFL and NASH, impaired peroxisomal polyunsaturated fatty acid (PUFA) metabolism and nonenzymatic oxidation is associated with progression to NASH.